Belgium : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
Belgium has effected a remarkable fiscal adjustment, best illustrated by the decline in its public debt. While benefiting from an appreciable decline in interest rates, most of the underlying consolidation reflected a considerable increase in the tax burden, one of the highest in the Organisation for Economic Cooperation and Development. This paper analyzes the social transfer system in Belgium. Belgium has a very accessible and equitable health care system. The system is characterized by high input levels and service volumes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet